Logic Pro X for dummies - English, Graham (Musician) (--For dummies., 2018)
Spend less time learning and more time recording Logic Pro X offers Mac users the tools and power they need to create recordings ready to share with the world. This book provides the know-how for navigating the interface, tweaking the settings, picking the sounds, and all the other tech tasks that get in the way of capturing the perfect take. Written by a Logic Pro X trainer who & rsquo;s used the software to further his own music career, Logic Pro X For Dummies cuts back on the time needed to learn the software and allows for more time making amazing recordings. Record live sound sources or built-in virtual instruments Arrange your tracks to edit, mix, and master Discover tips to speed the process and record on an iPad Make sense of the latest software updates A favorite among Logic Pro X beginners, this book is updated to reflect the ongoing changes added to enhance Logic Pro X & rsquo;s recording power.